THE GENUS BERTOLONIA (MELASTOMATACEAE) IN THE STATE OF BAHIA, BRAZIL - Bisewski, Gessica C.a.; F. Bacci, Lucas; Amorim, André M.; Goldenberg, Renato (Phytotaxa, 2022)
Bertolonia has 35 taxa, all endemic to the Atlantic Forest, among which many are microendemic or have restricted distribution. The plants are herbaceous, with scorpioid inflorescences and obtriquetrous (bertolonidium-type) capsules. The state of Bahia is one of the major diversity centers of Bertolonia, with 15 species, from which 12 are endemic. We present here a taxonomic treatment for the genus in the state of Bahia, with identification key, complete descriptions, distribution maps and illustrations for all the 15 species, all based on herbarium specimens, collections made by the authors, online databases and literature. We also provide here a lectotypification for B. violacea. Within the Bahian Atlantic Rainforest Bertolonia is distributed in three vegetation subtypes: ten species occur in montane rainforests, six in lowland rainforests and one in cloud forests. Of the 15 species of Bertolonia that occur in Bahia, eight were classified as Critically Endangered (CR), four as Endangered (EN), one as Vulnerable (VU) and two as Least Concern (LC), according to IUCN criteria.